Unconventional monetary policy and corporate bond issuance - Roberto A. De Santis; Andrea Zaghini (Goethe University Frankfurt, Center for Financial Studies (CFS), 2021)
We assess the effect and the timing of the corporate arm of the ECB quantitative easing (CSPP) on corporate bond issuance. Because of several contemporaneous mea- sures, to isolate the programme effects we rely on one key eligibility feature: the euro denomination of newly issued bonds. We find that the significant increase in bonds issuance by eligible firms is due to the CSPP and that this effect took at least six months to unfold. This result holds even when comparing firms with similar ratings, thus providing evidence that unconventional monetary policy can foster a financing diversification regardless of firms' risk profile. We also highlight the impact of the programme on the real economic activity. The evidence suggests that while all firms increased investment in capital expenditures and intangible assets, the CSPP induced eligible firms to invest in marketable and equity securities, to repurchase their own stocks, to hold cash and to carry out short-term investment.
urn:nbn:de:hebis:30:3-575790
Keywords: E52; G15; G32; 330; quantitative easing; CSPP; corporate bond market